Bio-inspired Maillard-Like reactions enable a simple and sensitive assay for colorimetric detection of methylglyoxal. Issue 55 (15th June 2015) - Wang, Shih-Ting; Lin, Yiyang; Spicer, Christopher D.; Stevens, Molly M.
Abstract : A simple and selective assay for methylglyoxal (MGO) detection was developed by combining a bio-inspired reaction with anti-aggregation of gold nanoparticles. Abstract : A simple and selective assay for detecting methylglyoxal (MGO), a metabolite associated with diabetes, was developed by combining a bio-inspired chemical reaction with the anti-aggregation of gold nanoparticles. This assay could detect MGO at as low as 1 μM by the naked eye and 0.05 μM by UV/vis spectrometry, within the clinical range marking oxidative stress in diabetes, and demonstrated high selectivity over other physiologically relevant ketones and aldehydes.